PENGARUH PROMOSI DAN KUALITAS LAYANAN MIE GACOAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN - erpurini, wala; Noerdiana, Yusep; Nurhasanah, Tiara; Handayani, Tri (JURNAL EKONOMI PERJUANGAN, 2024)
Customers at Bandung's Mie Gacoan Surya Sumantri were the subjects of this study. The goal of this study is to ascertain the relative and simultaneous effects of service quality and promotion on purchasing decisions at Bandung City's Mie Gacoan Surya Sumantri. Both the associative and descriptive research methods were employed in this study. The unit of analysis in this study is the individual, which is the consumer in Bandung's Mie Gacoan Surya Sumantri. There were 60 respondents in the study's sample.Multiple linear regression analysis is the analytical technique employed; the validity and dependability of the research instruments were also examined. The study's findings indicate that the independent variables (promotion and service quality) have a substantial, partial, and simultaneous impact on the dependent variable (purchasing decision).This research implies that in order to innovate about the products being sold or add new products that can be combined with Mie Gacoan products, the entire management team at Mie Gacoan must review the types of content—both images and videos—that are in line with expectations and what consumers want. They must also review product evaluations. Keywords: Promotion, Service Quality, Purchase Decision